Analisis Kadar Merkuri dan Hidrokuinon dalam Kosmetik Krim Pemutih yang Dijual di Online Shop - Adela Puspitasari; Indah Lestari; Devyana Dyah Wulandari (MPI (Media Pharmaceutica Indonesiana), 2018)
Mercury and hydroquinone are chemicals that are often added in cosmetic skin whitening. Both of these chemicals inhibit the formation of melanin, a pigment to protect skin against the dangers of ultraviolet rays that can cause negative effects on the skin. The long-term use of mercury and hydroquinone cause various toxic effects such as kidney, nerve, and brain disorders as well as blood cancer and liver cancer. The purpose of this study was to analyze mercury and hydroquinone in whitening creams sold in online shops. Each analysis was carried out using the Atomic Absorption Spectrophotometer (AAS) and UV-Vis Spectrophotometer. The results showed that of the 15 samples tested, 4 samples contained mercury and hydroquinone, while 11 other samples only contained hydroquinone. From this study it can be concluded that the fifteen samples of whitening cream tested were not safe and did not meet the requirements of the Regulation of the Head of the Republic of Indonesia Drug and Food Control Agency No. 18 of 2015 concerning Technical Material Requirements for Cosmetics.